PENGARUH SOSIALISASI PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN PELAPORAN SPT TAHUNAN WAJIB PAJAK ORANG PRIBADI - Nurdyastuti, Tri; Penawan, Adi (ProBank, 2018)
The puspose of this study to know effect of taxation socialization and tax sanctions on compliance reporting annual taxpayer personal taxpayer. Population in this research is all personal taxpayer registered at KPP Pratama Surakarta amounted 104,192 taxpayer. The sample was taken by using simple random sampling method as much as 100 respondents. The technique of analysis in this study using classical assumption test techniques and using multiple linear regression analysis test. The results of this study indicate that the socialization of taxation and taxation sanctions simultaneously affect taxpayer compliance. Partially taxation and taxation sanctions partially affect the taxpayer compliance of individuals registered at KPP Pratama Surakarta.Keywords: Socialization of taxation, Tax Sanctions, Taxpayer Compliance